2010
DOI: 10.2193/2009-130
|View full text |Cite
|
Sign up to set email alerts
|

Relative Effect of Food Supplementation and Natural Resources on Female Red Deer Distribution in a Mediterranean Ecosystem

Abstract: Supplementary feeding is a widespread game management practice in several red deer (Cervus elaphus) populations, with important potential consequences on the biology of this species. In Mediterranean ecosystems food supplementation occurs in the rutting period, when it may change mating system characteristics. We studied the role of food supplementation relative to natural resources in the spatial distribution, aggregation, and mean harem size of females in Iberian red deer (Cervus elaphus hispanicus) during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…Calf growth rate responded to animal variables in the same fashion that THI index did, that is, male growth rate was higher than female growth rate, calf growth rate increased with mother age, and decreased with mother weight and with calf age (Table 3). Tables 2 and 3 for three values of THI heat stress index (60,67,72) corresponding to its quantiles 0.1, 0.5 and 0.9; and three values of THIWS (96, 115, 126) corresponding to quantiles 0.1, 0.5 and 0.9; f: female calf (magenta); m: male calf (black).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Calf growth rate responded to animal variables in the same fashion that THI index did, that is, male growth rate was higher than female growth rate, calf growth rate increased with mother age, and decreased with mother weight and with calf age (Table 3). Tables 2 and 3 for three values of THI heat stress index (60,67,72) corresponding to its quantiles 0.1, 0.5 and 0.9; and three values of THIWS (96, 115, 126) corresponding to quantiles 0.1, 0.5 and 0.9; f: female calf (magenta); m: male calf (black).…”
Section: Plos Onementioning
confidence: 99%
“…A large number of Iberian red deer of the southern Spain populations live in fenced hunting estates [66] that precludes long distance and altitudinal movements. Besides, most of these populations are under unsustainable management that relies on food supplementation during mid and late summer, when plants quality and availability is insufficient to maintain high densities of deer [67,68]. Over-crowded deer populations aimed to hunting eco-tourism have a negative impact on forest renewal, which reduces natural shade availability in these populations.…”
Section: Behaviour As Mitigation Mechanism Of Heat Stressmentioning
confidence: 99%
“…Such aggregation has consequences for social behavior, as well as inter-and intra-specific interactions and stress levels. Aggression (Donohue et al 2013) and stress (Forristal et al 2012) both increase with ungulate density, and 4/5 studies observed higher levels of aggression associated with feeding (e.g., Pérez-González et al 2010).…”
Section: Evidence Of Unintended Effects Of Feedingmentioning
confidence: 99%
“…Mixed stands and stands of varying age generate a more heterogeneous habitat which results in more preferable light conditions for field layer vegetation compared to mono-specific and even age stands (Atlegrim and Sjö berg 1996, Lieffers et al 1999, Parlane et al 2006. The effect of forestry on field layer vegetation and damage level needs high priority in research, but silvicultural practices Gossow 1996, Vö lk 1999), establishment of preferred forage, and supplemental feeding have been shown to divert deer browsing from valuable trees (Campbell and Evans 1978, Nolte 1999, Gundersen et al 2004 and to affect deer distribution (Pérez-González et al 2010). Forageincreasing measures may thus also be used to attract ('pull') deer to sites where their presence is acceptable.…”
Section: Recommendations For Management and Researchmentioning
confidence: 99%